2018
DOI: 10.1097/sle.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Robotic Versus Open Thyroidectomy for Papillary Thyroid Cancer

Abstract: Our study results show that outcomes of robotic thyroidectomy may be similar to that of conventional thyroidectomy, with possible better preservation of the parathyroid blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Figure 2 shows that only T4 was performed in 100% of the cases and that Albumin, Calcium, Vitamin D and Parathyroid hormone were not performed in more than 50% of the cases. Similarly, preoperative and postoperative laryngoscopy was performed only in 1% and 24% respectively, thus making a complete analysis of the collected data impossible [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows that only T4 was performed in 100% of the cases and that Albumin, Calcium, Vitamin D and Parathyroid hormone were not performed in more than 50% of the cases. Similarly, preoperative and postoperative laryngoscopy was performed only in 1% and 24% respectively, thus making a complete analysis of the collected data impossible [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…To this effect the number of retrieved nodes needs to be evaluated. With respect to the aforementioned data on metastatic and retrieved lymph nodes, inter alia, a prospective comparison by Lee at al in 2014, 31 conclude that the number of dissected nodes with transaxillary robotic approach was comparable with that of open thyroidectomy, 31 37 thus fulfilling the criteria of oncological efficacy.…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have added that using the da Vinci System in the treatment of PTC decreases the rate of complications without reducing oncological efficacy. 40 It has also been reported that the outcomes of RT may be similar to those of OT, possibly even with better preservation of the parathyroid blood supply. 40 With respect to postsurgical complications among the analyzed techniques, Lee et al 41 noted some benefits of RT.…”
Section: Postsurgical Complicationsmentioning
confidence: 91%
“…40 It has also been reported that the outcomes of RT may be similar to those of OT, possibly even with better preservation of the parathyroid blood supply. 40 With respect to postsurgical complications among the analyzed techniques, Lee et al 41 noted some benefits of RT. In their opinion, the 15-fold magnification in RT may increase the visibility of very small vessels, thus protecting the blood supply of the parathyroid glands.…”
Section: Postsurgical Complicationsmentioning
confidence: 91%
See 1 more Smart Citation